A service evaluation of the diagnostic testing for mucous membrane pemphigoid in a UK oral medicine unit. (23rd June 2020) - Walton, Richard; Robinson, Max; Carrozzo, Marco
Abstract: Background: Mucous membrane pemphigoid (MMP) is an uncommon bullous disease typically involving the oral cavity. The most commonly used laboratory test for the diagnosis of MMP is direct immunofluorescence (DIF) on fresh perilesional tissue; however, the sensitivity of this test may be hampered by technical difficulties. Immune‐serological investigations can also be employed to render a diagnosis. The purpose of this paper was to present an evaluation of diagnostic testing for MMP within an Oral Medicine Unit in UK. Methods: A retrospective analysis of the medical records was undertaken for patients who had undergone biopsy and DIF testing from January 2016 to December 2018. Parameters analysed included clinical presentation, histopathological features, DIF, salt‐split skin indirect immunofluorescence, ELISA anti‐BP180 and BP 230 and HLA‐DQB1*03:01 findings. Results: Thirty patients (23 females and 7 males, mean age 66.8 years old) were diagnosed with MMP through a combination of histopathology and serological testing. Sixteen patients (53%) were DIF positive, whereas in 14 (47%), MMP diagnosis was achieved using immune‐serologic tests. HLA DQB1*03:01 status was undertaken in 15 DIF‐positive and 12 DIF‐negative patients, and HLA DQB1*03:01 was found in 73% and 58% of the cases, respectively. Conclusions: This service evaluation has shown that when DIF is informative, it remains the gold standard technique for diagnosis of MMP. However, we have also highlighted the value of serological testing for increasing diagnostic yield for patients with suspected MMP and the potential for HLA DQB1*03:01 as an adjunctive test for the evaluation of MMP.